PERAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN EFISIENSI PROSES BISNIS DI ERA ARTIFICIAL INTELLIGENCE - Kohar, Abdul (LPPM UNU CIREBON, 2024)
The advancement of Information Technology (IT) and its integration with Artificial Intelligence (AI) has brought about a major transformation in the modern business world. This study aims to comprehensively examine the role of IT and AI in improving business process efficiency, using a literature study approach and global case analysis. The results of the study show that the implementation of AI-based IT systems can automate routine processes, accelerate decision-making, and improve service accuracy. Case studies from companies such as Amazon, Siemens, and JP Morgan Chase show significant operational time savings, cost reductions, and increased customer satisfaction. The discussion also covers implementation challenges such as infrastructure readiness, data quality, and HR competency. This study recommends a gradual strategy in technology adoption, strengthening digital literacy, and an ethical approach in utilizing AI to ensure sustainable efficiency. These findings can be a strategic reference for organizations that want to accelerate digital transformation and increase competitiveness in the industrial era 4.0.